The Scramble for the Eastern Mediterranean Energy and Geopolitics - Talbot, Valeria (ISPI Publications, 2021)
Over the past few years, the Eastern Mediterranean has become a major hotspot for both natural gas and geopolitical competition. Natural gas discoveries in the last decade have attracted growing interest from regional countries and beyond. However, recent escalations in tensions and outright confrontations suggest that competition goes beyond the scramble for energy. Indeed, natural gas is just one of the factors that contribute to shaping security and geopolitical dynamics in the Eastern Mediterranean, which has emerged as a crucial strategic area in the broader Mediterranean and the Middle East. Moving from the analysis of these interconnected factors, this Report examines the strategy and the plethora of interests of regional and international players, as well as the interplay between cooperative and competitive dynamics in the region. What are the geopolitical, security, and energy interests of the countries involved? What are the implications on the regional security context of the moves and policies of regional and international powers?